A percepção de valor na visão do cliente: como a proposta de valor da organização detentora da Marca E é percebida pelos públicos-alvo - Souza, Daiana de (Universidade do Vale do Rio dos Sinos, 2020)
The present research aimed to understand how the target audiences perceive the value proposition of the organization which owns Brand E. This is an important step for the strategy, once the connection of the organization’s value proposition to he customer’s need is essential for the business continuity, for the definition of an exclusive value plan and for the structuring of the customer-oriented organization chain. In light of this perspective, the study has conducted an evaluation of value perception by some target-audiences (consumer, painters and clerks) who will serve as a subsidy for the assessment and adjustment of the value proposal and the further strategy operationalization to implement an exclusive value proposal, following for such intent the lessons of Porter (1996) referring to competition aiming uniqueness; along with the selecting process, supplying and communication of value in a set of benefits to the customers upon the customer’s value proposal which has been supported by Payne et al (2017) and structed by the value canvas, pointed out by Osterwalder et al (2019). The research was applied to the paint market, specifically the decoration painting segment, in the state of Rio Grande do Sul (reaching 7 cities) along with the target audiences. The quantitative step was applied to the final consumer and the qualitative step was done with all the target-audiences. At first, the intent was to understand the perception of the value of paint brands, limiting the study to the top five brands which were: Tintas Killing, Tintas Renner, Coral, Suvinil and Sherwin Williams and which in the presentation and analysis were categorized as Brands A, B, C, D and E, not necessarily in the respective order. In a second moment, it was verified what important features were perceived by the customer in conjunction with the painting brands. In the final and third objective, it was possible to understand how the researched audience perceived the Brand E’s value proposition. As a result, this research enabled the understanding of the attributes that in the perception of the target audiences represent the E Brand and the suggestion of improvements in the functional attributes and in those not perceived linked to the marketing compound. It also provided an understanding of audiences profile surveyed according to the value canvas, identifying priority actions to alleviate the “pain” of this audience through the set of marketing actions. And finally, the managerial implications built to support the organization which owns Brand E in directing effective actions in its strategic agenda, in view of the evident need for revision and adjustment in the value proposal.
Keywords: Estratégia; Percepção de valor; Proposição de valor ao cliente; Strategy; Value perception; Customer value proposition; ACCNPQ::Ciências Sociais Aplicadas::Administração